Polalanta Divorce Practices of the Banggai Tribe Community in Banggai Islands District in the Perspective of Islamic Law and Positive Law - Mutalib, Adiyanto; B, M Taufan; Malarangan, Hilal (State Islamic University Datokarama Palu, 2023)
This study discuss the practice of Polalantadivorce practice among the Banggai ethnic community from the perspectives of Islamic law and positive law in the Mansamat B Village, South Tinangkung District, Banggai Islands Regency.The aims of this study are examine factors drive the residents of Mansamat B Village, South Tinangkung District, Banggai Islands Regency to engage in Polalanta divorce practice, and to find out the perspective of Islamic and positive law in Polalanta divorce practice among the residents of the village. This study used a qualitative method with data collection techniques involving observation, in-depth interviews, and written document analysis. The data analysis techniques employed include data reduction, data presentation, data verification, and drawing conclusions. This study found that time efficiency and simplicity are significant factors motivating the Banggai ethnic community in Mansamat B Village to opt for divorce outside the Religious Court or Polalanta practice. Additionally, economic considerations also play a role, requires administrative expenses, which, despite subsidies for those less fortunate, are still perceived as significant by some. Hence, the choice to divorce outside the Religious Court is more appealing. Furthermore, a lack of legal awareness and personal issues contribute to this practice. We aso found that there are distinctions between positive law and Islamic law concerning divorce. Islamic law requires only formal witnessing, whereas positive law mandates court proceedings in the Religious Court. This provision is outlined in Article 39 paragraph (1) of Law No.1 of 1974, Article 65 of Law No.3 of 2006, and Article 115 of the Compilation of Islamic Law, stipulating that divorce can only take place before a court session after the court has attempted and failed to reconcile both parties.